Using Government Documents to Assess the Influence of Academic Research on Macroeconomic Policy - Thomas Mayer; Joaquim Silvestre (University of California, Department of Economics, 1999)
How can one tell whether academic research influences macroeconomic policy? One possibility is to look at government documents that set forth macro policy. This paper looks for such traces in U.S., European and Japanese documents. Because of ease of access it focuses on U.S. documents. Numerous traces of academic research can be found. But the road from government documents to policy is a precarious one; references and allusions to academic literature may merely be rationalizations for policies adopted for other reasons. Similarly, governments may use the results of academic research without this showing up in government documents.
Keywords: 330